ETNOMATEMATIKA GERAKAN TARI KRETEK KUDUS PADA PEMBELAJARAN MATEMATIKA - Nurus Sa’adah; Arghob Khofya Haqiqi; Putri Nur Malasari (ALGORITMA: Journal of Mathematics Education, 2021)
Ethnomathematics plays an important role to support a more meaningful concepts understanding in learning mathematics. The Kudus kretek dance is one of the entomathematics that supports understanding the concept of geometry. This study aims to examine the ethnomathematics of kretek dance which involves mathematical activities in learning mathematics. This research is a qualitative descriptive with an ethnographic approach. Data were collected by interview, documentation, and observation techniques. The results showed that the concept of the 900 angle was obtained through the movements of nampeni, milahi, melembar, mbathil, nggiling, sembahan, mrikso rokok, ngepak, pemasaran; the concept of acute angle is obtained through the movements of ngiteri, melembar, pemasaran; the concept of obtuse angle is obtained through ngayak, sembahan, ngiping, mrikso rokok, ngepak, pemasaran; and the concept of 1800 angle is obtained through a nggiling. The kretek dance is demonstrated in a certain beat accompaniment notation, the concept of two-dimensional geometry is found in the position of the feet of the dancers when they are doing the movement, while the concept of transformational geometry is obtained through twisting movements.